PENGARUH DESAIN INTERIOR PERPUSTAKAAN TERHADAP KENYAMANAN PENGGUNA DI PERPUSTAKAAN IAIS SAMBAS - Azwar Azwar (CV. ADIBA AISHA AMIRA, 2023)
The college library is a place to find knowledge and other sources of information. Libraries at tertiary institutions are an important place to get more attention so that they can support student learning processes, where they can find knowledge and other sources of information. Things that must be considered so that visitors feel at home in the library are elements of interior design so as to create comfort in the library, because interior design is important for designing a building such as a library. The design of the library building needs to pay attention to every function of the room, comfort, harmony and beauty of the room from an interior perspective. The library room will look comfortable for visitors when the space is arranged by paying attention to layout, color, air temperature, and lighting. The comfort of visitors or library users can be seen from interior design elements such as layout, color, air temperature, and lighting applied